2020
DOI: 10.21053/ceo.2019.01837
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Specific Differences in House Dust Mite (Dermatophagoides farinae)-Induced Mouse Models of Allergic Rhinitis

Abstract: Objectives. Limited information is available regarding strain-related differences in mouse models of allergic rhinitis induced by <i>Dermatophagoides farinae</i> (Der f1). In this study, we compared differences between two mouse strains and determined the optimal dose of Der f1 for allergic rhinitis mouse models.Methods. Forty-eight mice were assigned to the following six groups (n=8 per group): group A (control, BALB/c), group B (Der f1-sensitized BALB/c, 25 µg), group C (Der f1-sensitized BALB/c,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(33 reference statements)
2
10
0
Order By: Relevance
“…The expression of IL-5 mRNA in the nasal mucosa was not increased in IHDM-induced AR groups, but only a tendency to increase was observed, which could be a sign of the onset of the late phase allergic response in AR. These results are in agreement with those reported by Lee et al [28], who showed different expression levels of IL-5 mRNA in the nasal mucosa and mice splenocyte cultures. The absence of a significant change in IL-5 expression in the present study is presumably due to various chemotactic factors that caused a low expression of IL-5 in the nasal mucosa.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The expression of IL-5 mRNA in the nasal mucosa was not increased in IHDM-induced AR groups, but only a tendency to increase was observed, which could be a sign of the onset of the late phase allergic response in AR. These results are in agreement with those reported by Lee et al [28], who showed different expression levels of IL-5 mRNA in the nasal mucosa and mice splenocyte cultures. The absence of a significant change in IL-5 expression in the present study is presumably due to various chemotactic factors that caused a low expression of IL-5 in the nasal mucosa.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, the infiltration of eosinophils into the nasal mucosa resulted from an allergic reaction. Such an increase in eosinophil infiltration in the nasal mucosa has been reported previously [23,25,28,33].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“… 23 , 24 , 25 , 26 BALB/c mice immune responses tend to be Th2 response and are widely used for AR mice model. 27 However, C57BL/6 mice can be used as ILC2s mediated allergic inflammation, which reduce the influence of Th2 type adaptive immunity and better reflect the important role of innate immunity in respiratory allergic inflammation. 28…”
Section: Discussionmentioning
confidence: 99%